Technological Resources and the Reconfiguration of Medical Education - Muñoz-Cano, Juan Manuel; Maldonado Salazar, Teresita (Emerging Trends in Education, 2021)
The need for schoolwork in virtual settings because of the pandemic showed deficiencies in curriculum, pedagogy, and the use of technological resources. A qualitative, descriptive, hermeneutical study was conducted. The construction of Flexner’s medical education model, dating back to 1910, as well as the determinants that make it persist, were revised. The analysis was made from three approaches to the application of technological resources: classroom work, curriculum, and value education. The analysis showed the causes of the petrification of the curriculum model, which emerges from positivism and modernity. The effects of neopositivist and postmodernity on the model were reviewed as well. The dysfunctionality of the school process is explained by the model of functionalist structuralism. This shows how the transition to educational approaches to solving real-life problems has been hampered with the help of technological resources. Substantive modifications of form and content are needed so that technological resources are not just a means to bring the current model to the virtual.Keywords: B-learning; Curricular flexibility; Integrated curriculum; Problem-based learning; Clinically structured questions.